The Association Between Anxiety Symptoms and Sleep in School-Aged Children: A Combined Insight From the Children's Sleep Habits Questionnaire and Actigraphy. Issue 2 (4th March 2018) - Fletcher, Fay E.; Conduit, Russell; Foster-Owens, Mistral D.; Rinehart, Nicole J.; Rajaratnam, Shantha M. W.; Cornish, Kim M.
Abstract : The current study assessed the association between anxiety symptoms and sleep in 90 school-aged children, aged 6–12 years (Mage = 108 months, 52.2% male). The Children's Sleep Habits Questionnaire (CSHQ) and 14 nights of actigraphy were used to assess sleep. Anxiety was assessed using the Spence Children's Anxiety Scale (SCAS). A significant association was found between parent-reported anxiety symptoms and current sleep problems (i.e., CSHQ total scores ≥ 41). An examination of SCAS subscales identified a specific association between generalized anxiety disorder (GAD) symptoms and increased parental sleep concerns, including sleep onset delay, sleep duration, and daytime sleepiness. Regarding actigraphy, whilst anxiety was not associated with average sleep variables, a relationship was identified between anxiety and the night-to-night variability of actigraphy-derived sleep schedules.